Modeling near‐surface water redistribution in a desert soil - Luo, Y. (2020)
The goal of this study was to explore the use of the Peters–Durner–Iden (or PDI) instead of bimodal van Genuchten (or BVG) hydraulic functions to improve water redistribution simulations using HYDRUS‐1D for drier soils in desert environments. The PDI hydraulic functions take capillary and film flow into account, whereas BVG hydraulic functions are limited to capillary flow. By comparing measured with simulated water content data, we found that moisture redistribution simulations were improved by using PDI instead of BVG soil water retention and hydraulic conductivity functions. Compared with the BVG simulations, the PDI simulations particularly improved for drier soil conditions (i.e., volumetric water contents ranging from 6 to 10%; suction heads between pF 2 and pF 3.8, and saturation degrees between 19 and 32%, respectively) for the studied sandy soil of Scaling Environmental Processes in Heterogeneous Arid Soils (SEPHAS) Lysimeter 1. For pF >3, the PDI functions predicted higher hydraulic conductivity than the BVG functions, which confirmed the hypothesis that a hydraulic conductivity function, which can capture film flow, may improve moisture distribution simulations for dry soils. For pF between 2 and 3, however, simulation results improved due to the difference in the water retention rather than the hydraulic conductivity function.